Los últimos cazadores-recolectores en el occidente cantábrico - Ramil Rego, Eduardo; Blanco Sanmartín, Paz; Rodríguez Pérez, Maria (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2017)
This work is conceived like a state of the art on recent hunter-gatherers documented in the western end of the Cantabrian area. In it we have included deposits and other evidences ascribed at the end of the Upper Palaeolithic and at the Epipaleolithic-Mesolithic.